2015
DOI: 10.1007/978-3-319-20346-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Etching Methods for Producing Porous Silicon

Abstract: Porous silicon produced by electrochemical etching of silicon has become one of the most popular materials used in many scientific disciplines as a result of its outstanding and unique set of chemical and physical properties and cost-competitive fabrication processes. To understand the electrochemical mechanisms taking place in the course of the etching of silicon is a key factor to control and modify the structure of this versatile porous material. This makes it possible to produce a broad range of structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 155 publications
(184 reference statements)
1
10
0
1
Order By: Relevance
“…As illustrated in the tabulated results, the k obs was higher when using the composite prepared using the electrochemical deposition method. The present findings seem to be consistent with a previous study by Santos and Kumeria 25 for the MB degradation. Since the active sites are responsible for producing free radicals, with the increase of adsorbed MB in the active sites, a quicker photodegradation rate is achieved.…”
Section: Si +4hfsupporting
confidence: 94%
See 2 more Smart Citations
“…As illustrated in the tabulated results, the k obs was higher when using the composite prepared using the electrochemical deposition method. The present findings seem to be consistent with a previous study by Santos and Kumeria 25 for the MB degradation. Since the active sites are responsible for producing free radicals, with the increase of adsorbed MB in the active sites, a quicker photodegradation rate is achieved.…”
Section: Si +4hfsupporting
confidence: 94%
“…Therefore, preparing the surface of silicon before the deposition of TiO 2 is an important step. 25 Figure 1 shows the surface of the silicon wafer before and after the electrochemical etching assisted with laser projection. As shown in Fig.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…We prepared GBM homing nanoparticle formulation (SIWV-pSiNP­(ICG)) by functionalizing SIWV peptides on the surface of pSiNP-incorporating ICG in the pore (Figure a). The pSiNPs were prepared by the electrochemical etching of a high boron-doped-p ++ type silicon wafer, and ICG was incorporated within pSiNP via a calcium-assistant loading method using an ultrasonic bath. The ICG-loaded pSiNP formulation (pSiNP­(ICG)) was functionalized with SIWV peptides via a poly­(ethylene glycol) (PEG, M.W. = 5 kDa) linker.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The SEM images showed that the oxidized PSiP had irregular flat discoid shape ( Figure 1 a), and the statistical analysis of a SEM micrography of 150 particles determined a size distribution of 3 ± 1 µm ( Figure 1 b) and a thickness of ~400 nm. The sonication cycles, including the time and number of cycles, are the main factors in the resulting shape and particle size [ 21 , 22 ]. Moreover, the SEM analysis demonstrated that the PSiP surface presented homogeneous, cylindrical porous structures ( Figure 1 c) with an average pore size of 40 nm ( Figure 1 d); this confirms the presence of a mesoporous material.…”
Section: Resultsmentioning
confidence: 99%